Life quality indexes in neo-adjuvant chemotherapy in laryngopharynx cancer patients - Grin, N. V. (Journal of Education, Health and Sport, 2019)
Urgency. Cancer patients quality on life (QOL) is one on the important criteria for the effectiveness of the treatment estimation along with traditional clinical indicators: regression of the primary tumor focus and metastases, immediate and long-term results of treatment and survival. Materials and methods. 66 patients with morphologically confirmed squamous cell carcinoma of laryngopharynx II - IV (T2 - 4N0-2M0) stages have been examined. They got 3 cycles of neoadjuvant chemotherapy with 21 - 28 days intervals according to the following scheme: paclitaxel - 175 mg/m2, cisplatin – 40 mg/m2. The patients were divided into two groups. Both groups patients got detoxification: the group received arginine –containing drugs and enterosorbent, group of comparison got detoxification therapy with crystalloid solutions. QOL was assessed with the use of the EORTC QLQ-H and N35 questionnaire, Karnowski’s index and ECOG. The patients were examined in dynamics before treatment and during chemotherapy. Results. QOL of laryngopharynx malignant neoplasms patients correlates with objective clinical indexes, such as tumor regression - the more the tumor volume decreases, the better QOL of each individual patient and in the groups as a whole was, the average relapse-free survival period (median survival curve is 66 months for the main and 54 months for the group of comparison). Relapse-free survival period (in the main group it makes 87% of the total survival period, and in comparison - 72%). It is completely determined by the courses of neoadjuvant chemotherapy given. In this case, complex treatment of patients using arginine-containing drugs and enterosorption (the main group of patients) gives better results of QOL compared to the use of detoxification therapy with saline solutions in volume up to 1.5 - 2.0 liters according to the standard protocol. Karnowski’s index in the main group is 21.8%, and in the comparison group 4.4%; ECOG after three treatment cycles compared with the initial value decreased by 50.0%, while for patients in the comparison group this decrease was 21.4%. Conclusion. The use of QOL – indexes selected and conducting a comprehensive statistical analysis at each stage of treatment makes it possible to more objectively make research, draw the necessary conclusions, make reasonable adjustments to the treatment process, increase the evidence of medicine and the effectiveness of treatment.